(untitled) (Economic and Political Thought, 2019)
The article is aimed at evaluating international tax arbitrage application to optimise tax costs of using cars for business purposes by micro, small and medium-sized (MMSE) enterprises. The main part of the work is devoted to analysing economic and fiscal aspects of tax liabilities connected with registering cars in a related business entity operating in the Czech Republic. The evaluation of the issue is preceded by a presentation of an international tax arbitrage definition, a description of macroeconomic conditions for purchasing cars in Poland and an overview of the evolution of current and forthcoming fiscal regulations influencing conditions for using cars by domestic and foreign MMSE firms.